Photoregulation of Gold Nanoparticles Stabilized in a Diacetylenic Nanocapsule - Saowalak Somjid; Apiwat Chompoosor; Somdej Kanokmedhakul; Saowapak Teerasong (My University, 2017)
The results of releasing a drug in a burst are unpredictable and one of the inherent drawbacks of using nanocarriers. Here, photoresponsive cationic gold nanoparticles to stabilize diacetylenic nanocapsules enabling photoregulated release of payloads are reported. The fabrication of these nanocapsules relied on an electrostatic interaction of a negatively charged diacetylenic core and a positively charged gold nanoparticle shell. Gold nanoparticles with photoresponsive ligands on their surfaces act as both hydrophobic core stabilizers and gatekeepers of the nanocapsules, while their polydiacetylene cores serve as hydrophobic drug carriers that can be tuned using UV irradiation. The morphology of nanocapsules was analyzed using TEM and dynamic light scattering. The resultant nanocapsules had a spherical shape with an average diameter of 152.9 ± 6.7 nm. Upon UV irradiation, the nanocapsules lost their integrity and an encapsulated model compound was released through diffusion. The release of a hydrophobic molecule was irradiation time dependent and thereby controllable. This light-triggered release provides an alternative strategy for controlled drug delivery.
Keywords: Nanocapsules; Cationic polymerization; Nanocarriers; Polydiacetylene-based materials and applications